2006
DOI: 10.1101/gad.1470906
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation regulates long-range gene silencing of an X-linked homeobox gene cluster in a lineage-specific manner

Abstract: DNA methylation is a major epigenetic mechanism that has been suggested to control developmental gene regulation during embryogenesis, but its regulatory mechanisms remain unclear. In this report, we show that CpG islands associated with the X-linked homeobox gene cluster Rhox, which is highly expressed in the extraembryonic trophectoderm, are differentially methylated in a stage-and lineage-specific manner during the post-implantation development of mice. Inactivation of both Dnmt3a and Dnmt3b, DNA methyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
108
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 61 publications
(93 reference statements)
14
108
1
Order By: Relevance
“…Besides its role in imprinting, DNA methylation regulates gene expression in lineages of somatic cells during embryogenesis (Oda et al, 2006;Illingworth et al, 2008). Methylation of cytosines in CpG dinucleotides is a common epigenetic mark in vertebrate cis-regulatory regions (Deaton and Bird, 2011).…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%
“…Besides its role in imprinting, DNA methylation regulates gene expression in lineages of somatic cells during embryogenesis (Oda et al, 2006;Illingworth et al, 2008). Methylation of cytosines in CpG dinucleotides is a common epigenetic mark in vertebrate cis-regulatory regions (Deaton and Bird, 2011).…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%
“…Increases in sequence read length will not only aid unambiguous alignment of sequences but will dramatically improve the ability to study allelic variation in DNA methylation through colocalization of genetic and epigenetic polymorphisms within a single read. Moreover, while cells within an organism possess the same genome sequence, numerous studies have reported differential cytosine methylation in distinct cell types, indicating that an organism's cells may display high variability, akin to its diverse transcriptomes (Futscher et al 2002;Ching et al 2005;Bibikova et al 2006;Feldman et al 2006;Oda et al 2006;Weber and Schübeler 2007). Thus, with advances in sequencing technology it will be possible to explore this concept of a dynamic cytosine methylome via recording of this mark in each different cell type within an organism throughout development, under normal and disease states and in response to a variety of environmental influences.…”
Section: Single-base Methylomes By Genome-wide Shotgun Sequencingmentioning
confidence: 99%
“…This is further supported by studies examining RHOX regulation. Both mouse and human RHOX family members have been demonstrated to be strongly regulated by DNA methylation (25)(26)(27) and there is an association between RHOX hypermethylation and abnormal sperm in idiopathic infertile patients (14).…”
mentioning
confidence: 99%